Instructions on Building an Enlightened Society in the Socio-Political Views of Abu Nasr Farabi - Togaev Nodirjon Ergashevich (Researchparks Publishing, 2023)
This article examines the rich spiritual heritage of Abu Nasr Farabi, which contains advice on a just society, humanism, ethics and education. The author emphasizes that the socio-political, moral and humanitarian ideas of Farabi had a significant impact on the formation of the worldview of subsequent generations of scientists and thinkers, and also inspired people to a prosperous and creative life. The article explains that the introduction of Farabi's heritage into the consciousness of the people, especially into the thinking and worldview of the younger generation, is one of the most important tasks at the present time. It calls for the study and understanding of the ideas of Farabi to achieve the well-being and development of society.